2013
DOI: 10.1186/1471-2180-13-228
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of glycan interactions of clinical and avian isolates of Campylobacter jejuni

Abstract: BackgroundCampylobacter jejuni strain 11168 was demonstrated to have a broad specificity for eukaryotic surface glycosylation using glycan array analysis. The initial screen indicated that sialic acid and mannose are important binding partners after environmental stress, while galactose and fucose structures are likely to be involved in persistent infection.ResultsIn this broader study, five additional human/clinical isolates and six chicken isolates were fully assessed to determine their glycan binding capaci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 31 publications
0
16
1
Order By: Relevance
“…The high degree of specificity exhibited by H. pylori in its BgAg-binding interactions [ 28 , 29 ] is in contrast to our findings, and those of Day et al . [ 23 ], showing that C. jejuni can bind to a wide range of related antigens. This may reflect the contrast between the very restricted host range of H. pylori , which infects only humans, and that of C. jejuni , which is able to establish infection in a wide range of birds and mammals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The high degree of specificity exhibited by H. pylori in its BgAg-binding interactions [ 28 , 29 ] is in contrast to our findings, and those of Day et al . [ 23 ], showing that C. jejuni can bind to a wide range of related antigens. This may reflect the contrast between the very restricted host range of H. pylori , which infects only humans, and that of C. jejuni , which is able to establish infection in a wide range of birds and mammals.…”
Section: Discussionmentioning
confidence: 99%
“…Ruiz-Palacios and co-workers [ 21 , 22 ] showed that fucosylated sugar components in human breast milk could inhibit C. jejuni binding to HEp-2 cells in vitro and to human intestinal mucosa ex vivo , and also prevent C. jejuni infection of mice in vivo . Subsequent solid-phase assays confirmed the binding of C. jejuni strains, grown under host-like conditions, to a broad range of fucose (and galactose)-containing glycans, with different strains exhibiting differing binding profiles and avidities [ 21 , 23 ]; however, the identity of the C. jejuni lectin(s) responsible for this binding has not to date been determined. The common ABO histo-blood group antigens (BgAgs) comprise a complex and polymorphic group of fucosylated carbohydrates expressed on the surfaces of erythrocytes, but they are also highly expressed in the oro-gastro-intestinal (OGI) epithelium, as well as endothelial cells, and in secretions, such as milk, saliva and tears [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…These genes have been shown to be necessary for growth on fucose which is an abundant sugar found in mucin (Muraoka and Zhang, 2011), and C. jejuni NCTC11168 is one of several C. jejuni strains known to have this operon and to utilize fucose (Muraoka and Zhang, 2011; Stahl et al, 2011). Strains of C. jejuni from human and avian sources show affinities for fucose, suggesting its importance for persistence in the gut (Day et al, 2013). Despite the broad importance of fucose for colonization of the gut, fucose permease (fucP) knockout mutants have a colonization defect in mammals but not in the avian gut, suggesting additional substrates support C. jejuni colonization of the avian gut (Stahl et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…IMS isolated cells were labelled with CFDA-SE and glycan binding profile was analysed as described in Day et al . 56 . Full list of glycan structures see Table S6 .…”
Section: Methodsmentioning
confidence: 99%